Electric-Field-Driven Molecular Recognition Reactions of Guanine with 1,2-Dipalmitoyl-sn-glycero-3-cytidine Monolayers Deposited on Gold Electrodes - Alvarez-Malmagro, Julia (Langmuir : the ACS journal of surfaces and colloids, 2019)
Monolayers of 1,2-dipalmitoyl-sn-glycero-3-cytidine were incubated with guanine in a 0.1 M NaF electrolyte at the surface of a Langmuir trough and transferred to gold (111) electrodes using the Langmuir-Schaefer technique. Chronocoulometry and photon polarization modulation infrared reflection absorption spectroscopy were employed to investigate the influence of the static electric field on the orientation and conformation of the cytidine nucleolipid molecules on the metal surface in the presence of guanine and to monitor the molecular recognition of guanine with the cytosine moiety. When the monolayer is exposed to guanine solutions, the cytosine moiety binds to the guanine residue in either a Watson-Crick complex at positively charged electrode surfaces or a noncomplexed state at negative surface charges. The positive electrostatic field causes the cytosine moiety and the cytosine-guanine complex to adopt a nearly parallel orientation with respect to the plane of the monolayer with a measured tilt angle of ∼10°. The parallel orientation is stabilized by the interactions between the permanent dipole of the cytosine moiety or the Watson-Crick complex and the static electric field. At negative charge densities, the tilt of the cytosine moiety increases by ∼15-20°, destabilizing the complex. Our results demonstrate that the static electric field has an influence on the molecular recognition reactions between nucleoside base pairs at the metal-solution interface and can be controlled by altering the surface charge at the metal